KATP channel mutations in congenital hyperinsulinism: Progress and challenges towards mechanism-based therapies - ElSheikh, Assmaa; Shyng, Show-Ling (Frontiers in Endocrinology, 2023)
Congenital hyperinsulinism (CHI) is the most common cause of persistent hypoglycemia in infancy/childhood and is a serious condition associated with severe recurrent attacks of hypoglycemia due to dysregulated insulin secretion. Timely diagnosis and effective treatment are crucial to prevent severe hypoglycemia that may lead to life-long neurological complications. In pancreatic β-cells, adenosine triphosphate (ATP)-sensitive K+ (KATP) channels are a central regulator of insulin secretion vital for glucose homeostasis. Genetic defects that lead to loss of expression or function of KATP channels are the most common cause of HI (KATP-HI). Much progress has been made in our understanding of the molecular genetics and pathophysiology of KATP-HI in the past decades; however, treatment remains challenging, in particular for patients with diffuse disease who do not respond to the KATP channel activator diazoxide. In this review, we discuss current approaches and limitations on the diagnosis and treatment of KATP-CHI, and offer perspectives on alternative therapeutic strategies.